Investigation On Oxidation And Thermal Stability Of Jatropha Oil - Lubis, Abdul Munir Hidayat Syah; Ariwahjoedi, Bambang; Sudin, Mustafar (Penerbit UTM Press, 2015)
The application of jatropha oil as alternative lubricant basestock has emerged recently. However, the resistance to oxidation and thermal stability of this oil become a concern to its application as lubricant. In this study, the oxidation and thermal degradation of crude jatropha oil (CJO) have been studied. The oxidation of the CJO was investigated by air bubbling method. The viscosity and functional group changes due to oxidation were studied before and after oxidation test. The thermal stability of CJO was investigated by using Thermogravimetric analysis (TGA) method in O2 and N2 gases environment. Jatropha oil was found oxidized by autoxidation mechanism produces high molecular species which capable to increase viscosity of the oil. The TGA results shows that CJO thermally stable in the temperature below 168°C in O2 gas environment and below 225°C in N2 gas environment.